Penerapan Logika Fuzzy Metode Mamdani dalam Menyelesaikan Masalah Produksi Garam Nasional - Yulia Retno Sari; Maha Rani (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Indonesia is a maritime country. It is a country which has the second longest coastline in the world. With the long coastline, Indonesia can produce abundant marine natural resources like salt. Salt is a strategic commodity since it is needed to consumption, industry, pharmacy and oil drilling. Referring to the national salt balance issued by The Ministry of Marine Affairs and Fisheries (KKP) in 2014, it is stated that the acceleration of the increase in average salt consumption is inversely propotional to the amount of national salt production that is produced each year. This study is aimed to predict the amount of national salt production by using Mamdani Fuzzy logic method. The prediction result obtained are 1.400.000 tons in every year. The amount of production that will be predicted has independent variables namely rainfall, land area and salt requirements. By studying the factors that influence the amount of salt production, it is analyzed that the independent variable can explain the variation in the amount of salt production by 53% while the rest is explained by other variables. Therefore, these three variables must be optimized throught intensification and extensification which of course must be supported by policies issued by the government.